(untitled) (Bombay Hospital Journal, 2024)
35 y/o female came with complaints of pain in abdomen since 2 months and small swelling in the infraumbilical region increasing in size gradually over past 2 months. Pain was neither cyclical nor had any aggravating or relieving factors.Conservative management was tried without any relief. USG guided FNAC s/o paucicellular smears with occasional epithelial clusters ? Endometriosis ? Adenocarcinoma